A [3 + 2] cycloaddition/C-arylation of isatin N, N′-cyclic azomethine imine 1, 3-dipole with arynes. Issue 51 (19th August 2020) - Jin, Qiaomei; Zhang, Dongjian; Zhang, Jian
Abstract : A [3 + 2] annulation/C-arylation reaction of 1, 3-dipole 1 with arynes has been established for the synthesis of oxindole scaffolds. Abstract : A [3 + 2] annulation/C-arylation of isatin N, N ′-cyclic azomethine imine 1, 3-dipole 1 with in situ generated arynes has been established for the synthesis of 3, 3-disubstituted oxindole scaffolds. These highly functionalized scaffolds were assembled in moderate yields (up to 85% yield). The novel spirooxindole scaffolds displayed moderate antitumor activities, which represented promising lead compounds for antitumor drug discovery.